ChemInform Abstract: Synthesis and Thermodynamics of Porous Metal Oxide Nanomaterials. Issue 39 (September 2015) - Huang, Baiyu; Schliesser, Jacob; Olsen, Rebecca E.; Smith, Stacey J.; Woodfield, Brian F.
Abstract Review: 155 refs.